Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Would like to compute the following sum: $\sum_{j=1}^m (-1)^j \begin{pmatrix} m\\ j\end{pmatrix} \log(1 - j/n)$, where $1 \leq m < n$ are fixed integers. A similar sum has already been computed on Stackexchange at Limit of alternating sum with binomial coefficient, where the logarithmic term is $\log(a+bk)$; the answer is in terms of $r = a/b$ and involves the gamma function, $\Gamma(r)$. When I apply this to my situation, I get (as part of the answer) $a=1, b=-1/n$ and therefore, I get the term $\Gamma(r) = \Gamma(-n)$ which is not defined, since the gamma function has a pole there. Please help with the correct expression for the sum in my case.

share|cite|improve this question
In your sum, the term with $j=m$ is going to give $\log0$ if $m=n$. Maybe this is why that other formula doesn't work for you --- your sum inherently involves an undefined term. – Gerry Myerson Oct 12 '12 at 3:55
Sorry, I should have said that $m<n$. The problem still persists, though. – user44441 Oct 12 '12 at 5:53
@user44441: There's an edit link under the question. Please fix the question itself; people shouldn't have to read through the comments to understand the question. Note that the result in the other question is asymptotic for large $m$, so Gerry's point is still relevant, since the asymptotic expansion doesn't know whether you're excluding $m=n$. – joriki Oct 12 '12 at 6:16
You can get binomial coefficients using \binom mj or {m\choose j}. – joriki Oct 12 '12 at 6:28
Ok, thanks. My first post, so please excuse the mistakes. – user44441 Oct 12 '12 at 14:32

We can extend the sum to $j=0$ since the summand is $0$ for $j=0$. We have

$$ \begin{align} \sum_{j=0}^m(-1)^j\binom mjj^l &=\left.\sum_{j=0}^m\left(q\frac{\partial}{\partial q}\right)^lq^j\binom mj\right|_{q=-1} \\ &=\left.\left(q\frac{\partial}{\partial q}\right)^l(1+q)^m\right|_{q=-1} \\ &=(-1)^mm!\left\{{l\atop m}\right\}\;, \end{align} $$

where $\left\{{l\atop m}\right\}$ is a Stirling number of the second kind.

This vanishes for $0\le l\lt m$, so expanding the logarithm yields a power series in $1/n$ with leading term $1/n^m$:

$$ \begin{align} \sum_{j=1}^m (-1)^j\binom mj\log(1 - j/n) &= -\sum_{j=0}^m (-1)^j\binom mj\sum_{l=1}^\infty\frac1l\left(\frac jn\right)^l \\ &= (-1)^{m+1}m!\sum_{l=m}^\infty\left\{{l\atop m}\right\}\frac{n^{-l}}l\;. \end{align} $$

Formally, we can also write

$$ \sum_{j=0}^m(-1)^j\binom mj\log(1 - j/n)=\log\left(1-\frac qn\frac{\partial}{\partial q}\right)(1+q)^m\;, $$

but I'm not sure whether that's of any use.

share|cite|improve this answer
I was hoping for a closed form expression (like the post I am referencing) which will likely involve the Gamma function. Interestingly enough, the original problem where this comes from starts out with exactly the sum, $\sum_{l=m}^\infty \left\{ \begin{matrix} l\\m \end{matrix} \right\} \frac{1}{\ell n^{\ell}$. But this approach may yet be helpful, thanks. – user44441 Oct 13 '12 at 2:36
@user44441: Hehe, that's nice :-) And you're welcome. – joriki Oct 13 '12 at 2:49

Here is an asymptotic expression for the above sum; thanks for all the help. This took a little time to figure out.

$$ \begin{aligned} \sum_{j=1}^{m} (-1)^{j} \binom mj {\log(1 - j/n)} &= \sum_{j=1}^m (-1)^j \binom mj (\log(n-j) - \log n) \\ &= \sum_{j=1}^m (-1)^j \binom mj \log(n-m + m-j) - \log n \sum_{j=1}^m (-1)^j \binom mj \\ & = \sum_{m-j = 0}^{m-1} \left((-1)^{m - (m-j)} {m \choose m-j} \log((n-m) + (m-j))\right) + \log n\\ & = \sum_{k = 0}^{m-1} \left((-1)^{m-k} \binom mk \log((n-m) + k)\right) + (-1)^m (-1)^m\log n \\ & = (-1)^m \sum_{k = 0}^{m} \left((-1)^{k} \binom mk \log((n-m) + k)\right) \end{aligned} $$ Letting $r=n-m$, we now estimate $\sum_{k=0}^{m} (-1)^{k} \binom mk \log(r+k)$. $$ \begin{aligned} \sum_{k=0}^{m} (-1)^{k} \binom mk \log(r+k) &= \sum_{k=0}^{m} (-1)^{k} \binom mk \int_1^{r+k} \frac{1}{x}\, dx \\ &= \sum_{k=0}^{m} (-1)^{k} \binom mk \int_0^1\,\, \sum_{j=1}^{r+k-1} \frac{1}{x+j}\, dx \\ &= \int_0^1 \,\, \sum_{j=1}^{r+m-1} \frac{1}{x+j} \sum_{k = \text{max} \{j+1-r,0\}}^m (-1)^k \binom mk \, dx \\ &= \int_0^1 \,\, \sum_{j=1}^{r+m-1} \frac{1}{x+j} \cdot (-1)^{j-r+1} {m-1\choose j-r}\, dx \\ &= \int_0^1 \,\, \sum_{j=r}^{r+m-1} \frac{1}{x+j} \cdot (-1)^{j-r+1} {m-1\choose j-r}\, dx \\ &= \int_0^1 \,\, \sum_{i=0}^{m-1} \frac{(-1)^{i+1} {m-1\choose i}}{x+r+i} \, dx, \qquad i = j-r \\ &= \int_0^1 \,\, \frac{-\Gamma(m+1) \Gamma(r+x)}{\Gamma(m+r+x+1)}\, dx %&= -\Gamma(m+1) \int_0^1 \,\, \frac{\Gamma(n-m+x)}{\Gamma(n+x+1)}\, dx \end{aligned} $$ We have the following estimate for the ratio of Gamma functions: $\Gamma(N)/\Gamma(N+x) = N^{-x}(1 + O(1/N))$. Therefore, $\displaystyle{\Gamma(r+x)/\Gamma(r+x+m+1) = (r+x)^{-m-1} (1 + O(1/r))}$. Plugging this back into the previous equation and integrating, we get \begin{equation} \sum_{k=0}^{m} (-1)^{k} \binom mk \log(r+k) = \frac{-\Gamma(m)}{m} \left( \frac{1}{r^m} - \frac{1}{(r+1)^m} \right) ( 1 + O(1/r) ) \end{equation} where $r=n-m$. Putting all this together we have: \begin{equation} \sum_{j=1}^{m} (-1)^{j} \binom mj \log(1 - j/n) = (-1)^{m+1} \frac{\Gamma(m)}{m} \left( \frac{1}{(n-m)^m} - \frac{1}{(n-m+1)^m} \right) ( 1 + O(1/(n-m)) ) \end{equation}

share|cite|improve this answer

Yesterday, I posted my answer by mistake on the other post while I was supposed to post it here. Anyways, your case is a special case of the case, we are going to deal with.

Recalling the identity of Stirling numbers of the second kind in terms of the binomial,

$$\left\{\begin{matrix} n \\ m \end{matrix}\right\} = \frac{1}{m!}\sum_{j=0}^m (-1)^{m-j}{m \choose j } j^n\,. $$

Writing the sum as $$ \sum\limits_{k=1}^{n} (-1)^k {n \choose k} \ln(a) + \sum\limits_{k=1}^{n} (-1)^k {n \choose k} \ln(1+\frac{b k}{a})$$

$$ -\ln(a) + \sum\limits_{k=1}^{n} (-1)^k {n \choose k} \ln(1+\frac{b k}{a}) \,.$$

Expanding the $\ln(1+\frac{b k}{a})$ in terms of its Taylor series and interchanging the order of summation gives $$ -n!\,\sum_{m=1}^{\infty}{\left(\frac{b}{a}\right)}^{m}\frac{1}{m} \left(\frac{1}{n!}\sum\limits_{k=1}^{n} (-1)^{m-k} {n \choose k} k^m \right) = -n!\,\sum_{m=1}^{\infty}\left\{\begin{matrix} m \\ n \end{matrix}\right\} {\left(\frac{b}{a}\right)}^{m}\frac{1}{m} $$

$$ = -n!\,\sum_{m=1}^{\infty}\left\{\begin{matrix} m \\ n \end{matrix}\right\} {\left(\frac{b}{a}\right)}^{m}\frac{1}{m} \,,$$

$$ \Rightarrow \sum\limits_{k=1}^{n} (-1)^k {n \choose k} \ln(a+bk) = -\ln(a) -n!\,\sum_{m=1}^{\infty}\left\{\begin{matrix} m \\ n \end{matrix}\right\} {\left(\frac{b}{a}\right)}^{m}\frac{1}{m} \,. $$

share|cite|improve this answer
Isn't this a duplicate of @joriki's answer, posted 11 hours earlier? – Did Oct 12 '12 at 23:05
@did:Did you read what I wrote at the top of my answer. – Mhenni Benghorbal Oct 12 '12 at 23:09
I did. And? $ $ – Did Oct 12 '12 at 23:21
Good that you did. – Mhenni Benghorbal Oct 12 '12 at 23:26
Do you consider you answered, even partly, my first comment? If not, why do you consider unnecessary to do so? Attitudes have consequences, you know... – Did Oct 13 '12 at 8:28

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.